The Use of Mini-Plates for the Treatment of a High-Angle, Dual Bite, Class II Malocclusion - Celha Borges Costa Alves; Maria Alves Garcia Santos Silva; José Valladares Neto (Galenos Yayinevi, 2019)
To present a case report of an orthodontic treatment of a high-angle, dual bite, Class II malocclusion without extractions and with the use of mini-plates. Class II malocclusion treatment protocols vary according to the morphological component of the malocclusion and the magnitude and direction of craniofacial growth. It is generally agreed that the cooperation of the patient and careful planning of anchorage are the key determinants of successful treatment. Protrusion of the upper and lower lip and a retrognathic mandible were the patient's chief concerns. The patient had learned to project her mandible forward to disguise the overjet. The patient's parents elected to correct the malocclusion with the use of bilateral infrazygomatic mini-plates. Pre-treatment condylar stabilization with an orthotic established a stable centric relation position, followed by mounting of the models on a semi-adjustable Panadent articulator. This allowed diagnosis and treatment planning from a stable condylar position and eliminated possible misdiagnosis due to the dual bite. Distal retraction and vertical control of the upper teeth enabled correction of the Class II malocclusion with minimal patient cooperation. Mini-plate-assisted treatment corrected the excessive overbite and overjet. The patient completed treatment with a stable occlusion and no longer postured her jaw forward. The parents and patient were completely satisfied with the positive treatment outcome. A 2-year follow-up confirmed the clinical stability.